A transmissão da empresa e seu regime jurídico - Antunes, José Engrácia (2008)
This essay aims at showing and characterization modes and legal instruments of enterprise transfereing highlighting that which, according to me, is the future crucial distinction in its legislative treatment, that is, the distinction between "asset deals" and "Share deals".